The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.coph.2007.04.005
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcysteine—a safe antidote for cysteine/glutathione deficiency

Abstract: Glutathione (GSH) deficiency is associated with numerous pathological conditions. Administration of N-acetylcysteine (NAC), a cysteine prodrug, replenishes intracellular GSH levels. NAC, best known for its ability to counter acetaminophen toxicity, is a safe, well-tolerated antidote for cysteine/GSH deficiency. NAC has been used successfully to treat GSH deficiency in a wide range of infections, genetic defects and metabolic disorders, including HIV infection and COPD. Over two-thirds of 46 placebo-controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
460
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 586 publications
(480 citation statements)
references
References 42 publications
15
460
0
5
Order By: Relevance
“…We did not observe any severe side effects, such as anaphylactoid reaction, and the prevalence of possible NAC adverse drug reactions was similar in both study groups. [16][17] It is in line with the study by Barkholt et al 18 in which no infusionrelated toxicity or side effects were reported following administration of high doses of parenteral NAC in hematopoietic SCT patients. We used the injectable form of NAC because oral administration of 100 mg/kg/day of NAC in the form of 200 or 600 mg tablets seemed to be unfeasible.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We did not observe any severe side effects, such as anaphylactoid reaction, and the prevalence of possible NAC adverse drug reactions was similar in both study groups. [16][17] It is in line with the study by Barkholt et al 18 in which no infusionrelated toxicity or side effects were reported following administration of high doses of parenteral NAC in hematopoietic SCT patients. We used the injectable form of NAC because oral administration of 100 mg/kg/day of NAC in the form of 200 or 600 mg tablets seemed to be unfeasible.…”
Section: Discussionsupporting
confidence: 84%
“…These side effects abate shortly after NAC discontinuation or administration rate reduction. 16,17 In a study using high doses of parenteral NAC for early liver toxicity of allogeneic hematopoietic SCT, no infusion-related toxicity or side effects were reported. 18,19 Few animal and clinical studies exist on the efficacy of NAC for prevention of radiation-induced OM and they have shown promising results in reducing OM severity using a topical formulation.…”
Section: Introductionmentioning
confidence: 99%
“…(Glutathione interacts with GCL allosterically to inhibit its activity (Richman and Meister 1975)). An efficient way to achieve this, without increasing protein intake per se, is to supplement with N-acetylcysteine (NAC), a well-absorbed and chemically stable compound that is rapidly cleaved to liberate free cysteine soon after it is absorbed (Atkuri et al 2007;Dodd et al 2008). (Cysteine per se is too unstable to be employed as a concentrated supplement, and the cystine which it readily gives rise to is poorly absorbed.)…”
Section: Strategies For Boosting Glutathione Synthesismentioning
confidence: 99%
“…compound with antioxidant and anti-inflammatory properties, exhibiting effects on microcirculation 12 . NAC acts directly as an antioxidant, by deactivating reactive oxygen species, or indirectly, by replacing intracellular glutathione stores.…”
Section: N-acetylcysteine (Nac) Is a Thiol-containingmentioning
confidence: 99%